2010
DOI: 10.1007/s00284-010-9592-7
|View full text |Cite
|
Sign up to set email alerts
|

Design, Recombinant Expression, and Antibacterial Activity of the Cecropins–Melittin Hybrid Antimicrobial Peptides

Abstract: In order to evaluate their antibacterial activities and toxicities, the cecropins-melittin hybrid antimicrobial peptide, CA(1-7)-M(4-11) (CAM) and CB(1-7)-M(4-11) (CBM), were designed by APD2 database. The recombinant hybrid antimicrobial peptides were successfully expressed and purified in Pichia pastoris. Antimicrobial activity assay showed that both of the two hybrid antimicrobial peptides had strong antibacterial abilities against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…These hybrids formed ion-permeable channels in model lipid membranes. Hybrid peptides have improved antimicrobial activ- ities against Gram-positive bacteria, with a significant reduction of the toxicity that comes from melittin (2,29). Nisin, which is a 34-residue peptide that can be isolated from the nonpathogenic bacterium Lactococcus lactis, belongs to a special group of AMPs called bacteriocins that, because of containing unusual amino acids (lanthionine and methyl lanthionine residues), emerged as one of the most extensively studied lantibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…These hybrids formed ion-permeable channels in model lipid membranes. Hybrid peptides have improved antimicrobial activ- ities against Gram-positive bacteria, with a significant reduction of the toxicity that comes from melittin (2,29). Nisin, which is a 34-residue peptide that can be isolated from the nonpathogenic bacterium Lactococcus lactis, belongs to a special group of AMPs called bacteriocins that, because of containing unusual amino acids (lanthionine and methyl lanthionine residues), emerged as one of the most extensively studied lantibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to obtain high purity and yield of melittin will be the key and difficult point for future research. Some scholars expected to obtain high yield and purity of melittin by biological fermentation engineering technology, their work suggested that more engineered expression systems should be develop to reduce the cost of acquiring melittin [43][44][45][46]. Secondly, Chemical modification of structure of melittin or combined with other protein could enhance the biological stability.…”
Section: Discussionmentioning
confidence: 99%
“…In the same trend, even better hybrids were designed and produced in Pichia pastoris, with higher antimicrobial activity and no hemolytic activity. Therefore, a potential application was proposed (Cao et al, 2010).…”
Section: Colicinsmentioning
confidence: 99%